Study on Security Testing-as-a-Service (TaaS) in Cloud Environment - Ponkoodalingan, Kannan; Gai, VIncent; Deshinta, Arrova Dewi (INTI International University, 2018)
Cloud computing in the 21st century is nothing new in the IT field. Cloud computing is a myriad group of servers where it stores data remotely in a data center. With today’s technology, cloud computing has changed on how the way of a user getting resources and managing services and solutions. This leads to the offering of Software-as-a-Service (SaaS) for clouds where it eases the user from using daily applications. However, the improvement in technology is also directly proportional towards the increase of security threats towards cloud environment. Thus, in order to provide the cloud services successfully, the cloud needs to be tested and audited before deploying to the public. This research aims to critically study on the threats that may jeopardize the cloud and provide a solution on how to improve the security of cloud computing. Two scenarios are included in the study with its virtualization. The data and network integrity attack are conducted as part of security testing.